Review of a specialist Rett syndrome clinic from 2003 to the COVID pandemic: clinic experience and carer perspectives - Emily Sloper; Megan Hunt; Angus John Clarke (Orphanet Journal of Rare Diseases)
Abstract Background We have held a ‘trouble-shooting’ clinic for Rett syndrome patients from 2003 until the COVID pandemic in 2020. The clinic was multidisciplinary, including clinical genetics, paediatric neurology, adult learning disability psychiatry and physiotherapy. Access to specialist communication support and eye-gaze equipment was also often available. We have reviewed the files of patients seen in the clinic and conducted a survey of parents’ and carers’ satisfaction with the clinic and their experiences during COVID. Results Of the 117 patients seen in the clinic, records were reviewed of 103 (97 female, six male) who attended a total of 123 appointments. The records were unavailable for 14 patients. The most common reasons for referral were assessment of ‘episodes’ of uncertain nature (possibly epileptic, possibly autonomic), the wish for a general review by an experienced team, and questions about the diagnosis. We discuss the nature of the advice we were able to provide and offer some brief case vignettes. We wrote to the parents or carers of all patients seen and 63 respondents were willing to be interviewed about the clinic and their experiences during COVID. Respondents were generally complimentary about the clinic team, emphasising the value of a specialist clinic for those affected by a rare condition. Respondents gave insight into the range of problems experienced during COVID, especially the isolation resulting from the withdrawal of services, demonstrating the value of community support. Some respondents mentioned the shift to remote consultations, which they hoped would continue after COVID for its convenience. However, others talked about how difficult it is in a remote consultation to explain the problems of the affected family member to professionals who do not know the patient or know about Rett syndrome. Conclusions Our findings demonstrate the value of a disease-specific clinic provided by staff experienced with the particular rare condition. Meeting the needs of patients with ultra-rare conditions presents additional challenges. We have also found that the shift to holding a virtual clinic during COVID brought the benefit of convenience but was unsatisfactory in other ways, as it makes clinical assessment more difficult and fails to overcome the sense of isolation during a pandemic.